Development of Software Process Guideline to Improve Software Process Using ISO IEC 29110 5 12 Software Implementation Process (Open International Journal of Informatics, 2021)
Many software development organizations all over the world are small and medium enterprises. Successful implementation of Software Process Improvement (SPI) methodologies in very small and software enterprises (VSEs) is generally not possible because such organizations cannot invest the cost of implementing these programs. There are various SPI methodologies to address these issues, which have also been deployed in organizations. In this study, recent and significant ISO IEC 29110 SPI methodologies and its Software Implementation (SI) process are compared with the current software team's current practices. The comparison result serves as the basis for developing a process guideline that best suits the software team. The process guideline will facilitate the maturity of software process and standardization within the software team, contributing to software product quality produced by the software team in the future.
Keywords: Software Process Improvement; Software Implementation Processes; ISO/IEC 29110; Very Small Software Enterprises; SPI Methodology